ANALISIS PENGARUH DISPLAY PRODUK, PROMOSI BELOW THE LINE, DAN EMOSI POSITIF TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF PADA SRIRATU DEPARTEMENT STORE - Nugraheni, Rini; I’sana, Allan Dwi (Faculty of Economics and Business Diponegoro University, 2013)
Recently in retail market, there was a phenomenom that indicated the marketdecrease. And then some company make a new strategy to adapt with the change of market. One of strategy was to increase the unplanned purchasing/impulse buying. Unplanned purchasing behavior (unplanned buying) or impulsive buying is something interesting for producers and retailers,because it’s a huge market share in the modern market. Then, the phenomenon of